Educação musical, Pedagogia e estágio supervisionado: encontros formativos presenciais e virtuais - Lemes, Daffny Cristina Molina (2020)
This dissertation is linked to Education and Arts Research Line (LP4) of Graduate Program in Education at Federal University of Santa Maria (PPGE/UFSM), to research group FAPEM – Formation, Action and Research in Music Education and to Musical Education Laboratory of Education Center (LEM/CE). In this investigation, we sought to understand how Music Education can be enhanced in the planning of student-trainees of Pedagogy/Night course, from a training group. For that, it was outlined as specific objectives: problematize Music Education from the perspective of student-trainees who are in training group; to know what move student-trainees of Pedagogy/Night course in musical practices at the Basic Education school; and understand the formative contributions resulting from the constitution of a group, in present meetings and through digital technologies. The research had as methodological support the educational action-research (BELLOCHIO, 2000; CARR; KEMMIS, 1988; KEMMIS; MCTAGGART, 1988), which was developed through formative meetings, in person and digital technologies, in Music Education, with a group of student-trainees of Pedagogy Course Full Night at UFSM. The literature review was based on Souza, Z. (2018), Bellochio and Souza (2017); Cernev (2015; 2013); Werle (2014; 2010), Bellochio and Garbosa (2014) Gohn (2013), Cuervo (2012); Oliveira (2011) and others. The formative meetings were designed and organized by the participants, in an active, participatory and collaborative way, during the group meetings, in person and virtual. The investigative development was driven by the self-reflective spiral (KEMMIS; MCTAGGART, 1988). As instruments of data production, oral and written narratives were used. Among the results are the reflections resulting from the analysis of four cycles, which are considered dilemmatic cycles experienced by the participants during ES and their teaching performance in Basic Education. They are: (1) Teaching in Music and its Relationships; (2) Musical repertoire and formative resources; (3) School context and links between learning in pedagogical practice; (4) Time and its mediations. The search for understanding and overcoming these aspects was essential for discussions and reflections and, in addition, it became a conductive device of actions and planning in Music Education. The constitution of a musical, participatory and collaborative formative space proved to be a locus of dialogues and exchanges of teaching experiences, sharing different perspectives and getting closer through the dilemmas shared in the group. Thus, it was possible to perceive the expansion of ways of thinking and making music during the development process of ES and the construction of teaching in Music.